« Évaluation de l'effet de l’extrait du laurier-rose (N.Oléandre) comme un antifongique puissant dans la région de Mostaganem » - ATIA, Khadîdja; BEGLOUL, Mamia (My University, 2024)
The study focuses on the extract of oleander (Nerium oleander), also known as oleander in Algeria, a medicinal plant from the Apocynaceae family. Although mainly used as an ornamental plant, this species was collected in the Oued El Kheir region (Mostaganem) to evaluate its fungicidal potential against Fusarium and Alternaria alternata fungi. Chemical analyses revealed the presence of flavonoids, tannins, saponosides, glycosides, sterols, and terpenoids in the extract obtained from the aerial parts (leaves) of the plant by maceration. The extract showed strong antibiotic activity against the moderately susceptible Alternaria alternata strain (41.18% inhibition) compared to the resistant Fusarium strain (14.63% inhibition). This research indicates that N. oleander extract can be used as a biofungicide to prevent fungal diseases in plants. The difference in inhibition depends on various factors, including the concentration of the plant extracts studied.
Keywords: Oleander (N.Oleander); Fungicide; Flavonoids; tannins; saponosides; glycosides; sterols and terpenoids; Antifungal activity; Alternaria alternata; Fusarium; Biofungicide; Concentration of plant extracts